Evidence-Based Clinical Recommendations on the Appropriateness of Prescriptions and Diagnostic Tests in Paediatric Allergology: Focus on IgE-Mediated and Non-IgE Mediated Food Allergy, Eosinophilic Gastrointestinal Disease, Urticaria, Angioedema and Atopic Dermatitis - Valentina Fainardi; Matteo Riccò; Rachele Antignani; Simona Bellodi; Mauro Calvani; Fabio Cardinale; Elena Chiappini; Maria Angiola Crivellaro; Daniela Cunico; Massimiliano Esposito; Antonella Giudice; Roberto Grandinetti; et al. (Children, 2026)
Background: Appropriate diagnostic testing is essential to quality pediatric allergy care, affecting diagnostic accuracy, treatment decisions, resource use, and patient outcomes. This study aimed to develop evidence-based recommendations for specialist consultations and diagnostic investigations in children with food allergies, eosinophilic gastrointestinal diseases, urticaria, angioedema, and atopic dermatitis. Methods: A multidisciplinary panel convened for the Italian National Institute of Health formulated and prioritized clinical questions using the PICO framework and structured expert consensus. A systematic review of the literature from 2015 to 2026 informed the recommendations, with certainty of evidence assessed using GRADE methodology. Results: In food allergy, sensitization tests alone are insufficient for diagnosis, while oral food challenges remain central to diagnostic confirmation. Endoscopic biopsies are essential for diagnosing eosinophilic gastrointestinal diseases. In chronic urticaria, specialist consultation is recommended, whereas routine allergy testing should be avoided without a suggestive clinical history. In angioedema, distinguishing histaminergic from bradykinin-mediated forms is critical, with targeted laboratory testing for hereditary or acquired conditions. In atopic dermatitis, standardized severity assessment should guide management and consideration of biologic therapies, while patient and family education represent key components of care. Conclusions: These recommendations provide a framework for standardized pediatric allergy diagnostic pathways, aiming to improve quality and equity of care while reducing unnecessary investigations and optimizing healthcare resource use.